Barriers to Creativity, Market Knowledge Acquisition and Market Performance: The Moderating Role of Network-Building Capability in SME Sector - Fansuri Munawar; Rini Handayani (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Small and medium enterprises (SMEs) play a crucial role in economic development, but various barriers often hinder their ability to drive innovation through creativity. This study aims to investigate these barriers and their impact on market performance, with a focus on the moderating role of network-building capability and the mediating role of market knowledge acquisition.Purpose: The primary objectives of this study are to (1) identify environmental and management barriers that hinder creativity in SMEs, (2) explore how market knowledge acquisition mediates the relationship between creativity and market performance, and (3) evaluate the role of network-building in moderating the impact of these barriers.Design/methodology/approach: The study used a survey-based approach, collecting data from 195 SME owners or managers across nine manufacturing sub-sectors in Bandung, Tasikmalaya, and Majalengka. Data analysis was performed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 3.0.Findings/Result: The results show that environmental barriers are not significant on creativity, but management barriers significantly inhibit creativity. Then, creativity positively affects market knowledge acquisition and market performance. In addition, market knowledge acquisition is a mediator between creativity and market performance, and network-building capability effectively moderates the negative impact of management barriers on creativity.Conclusion: SMEs should focus on enhancing their network-building capabilities to mitigate management barriers that hinder creativity. Moreover, continuous market knowledge acquisition is critical for turning creative ideas into practical innovations that can improve market performance.Originality/value (State of the art): This study provides insights into the managerial and environmental barriers faced by SMEs in fostering creativity and highlights the importance of network-building and market knowledge acquisition. It contributes to the literature by offering an understanding of how SMEs can overcome barriers to improve market performance. Keywords: barriers, creativity, market knowledge acquisition, market performance, SME